Political Participation Behavior and Democracy Level of Bangkok Citizens - paoin, nuttakrit (King Prajadhipok’s Institute Journal, 2020)
Study of political participation among citizens is imperative for democratic development. This research aims to inquire regarding political participation of Bangkok citizens. In this regard, this study presents many interesting findings. Level and pattern of political participation can differentiate levels of democracy in different aspects of Bangkok civilian. Specifically, Bangkok citizenscivilian who participates in politics only via media and never directly participates directly in real politics have significantly has lower level of democracy than ones who directly participates directly. significantly. Moreover, when focusing on three aspects of direct political participation;(1) participating in political campaigns, (2) participating in political protests, and (3) participating in general elections by voting, the first and the third aspects can differentiate participating citizens them those who have never had direct experience in direct political participation. However, the second aspect, citizens’ participation in political protest, in unrelated to a citizen’s level of democracy compared to that of a citizen who has never had direct experience in direct political participation.